2021
DOI: 10.1158/1078-0432.ccr-20-3136
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Biomarker Analysis of Camrelizumab in Combination with Apatinib in Patients with Advanced Nonsquamous NSCLC Previously Treated with Chemotherapy

Abstract: Purpose: Our preclinical work suggests that appropriate angiogenesis inhibition could potentiate PD-1/PD-L1 blockade via alleviating hypoxia, increasing infiltration of CD8+ T cells and reducing recruitment of tumor-associated macrophages. We hereby conducted a clinical trial to evaluate this combination in pretreated patients with advanced non–small cell lung cancer (NSCLC). Patients and Methods: The study included phase Ib … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
97
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 45 publications
15
97
1
Order By: Relevance
“…However, the OS curves of the three groups overlapped extensively. Several studies have shown that anti-angiogenic agents act synergistically with PD-1/ PD-L1 inhibitors to improve the low efficacy of ICI monotherapy, with an ORR of~30% (21,22). The combination treatments increased infiltration of CD8+ T cells, reduced recruitment of tumor-associated macrophages, reversed inhibition of DC maturation, and promoted the development of an angiostatic and immune system-activating tumor microenvironment (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the OS curves of the three groups overlapped extensively. Several studies have shown that anti-angiogenic agents act synergistically with PD-1/ PD-L1 inhibitors to improve the low efficacy of ICI monotherapy, with an ORR of~30% (21,22). The combination treatments increased infiltration of CD8+ T cells, reduced recruitment of tumor-associated macrophages, reversed inhibition of DC maturation, and promoted the development of an angiostatic and immune system-activating tumor microenvironment (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study reported that apatinib had encouraging clinical activity with a median PFS of 5.4 months and a median OS of 10.0 months in extensive-stage small-cell lung cancer patients who had more than two prior chemotherapy treatment failures with manageable toxicity ( 26 ). The combination of an anti-PD-1 antibody (SHR-1210) and apatinib (250 mg) treatment showed promising efficacy with acceptable toxicity in patients with hepatocellular carcinoma, gastric cancer, esophagogastric junction cancer, and advanced non-squamous NSCLC by modulating tumor immune microenvironment ( 27 , 28 ). A retrospective study of 23 metastatic colorectal cancer patients demonstrated that the combination of apatinib with chemotherapy was more effective treatment than apatinib monotherapy ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A phase III trial has shown that camrelizumab plus chemotherapy as first‐line treatment can bring benefit to advanced or metastatic nonsquamous NSCLC 10 . Pilot studies have demonstrated that the combination treatment enhanced the anticancer capability as higher‐line therapy in advanced NSCLC patients previously treated with chemotherapy 11,12 . Additionally, for advanced hepatocellular carcinoma and cervical cancer, camrelizumab plus apatinib is also a potential option.…”
Section: Discussionmentioning
confidence: 99%
“…Promising anticancer activity has also been observed in pretreated advanced NSCLC patients. Another phase II trial has also shown the efficacy of camrelizumab in combination with apatinib on NSCLC after failure of first‐line chemotherapy, with an objective response rate (ORR) of 30.9%, median PFS of 5.7 months, and median OS of 15.5 months 12 …”
Section: Introductionmentioning
confidence: 99%